Hidradenitis suppurativa: a review - Barrera-Mera, Baltazar; Granados-Romero, Juan José; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Palacios-Rodríguez, Patricia M.; Mendizabal-Velazquez, Alondra; González-Martínez, Itaty C.; Brito-Brito, Nicolás R.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I. (International Journal of Research in Medical Sciences, 2023)
Hidradenitis suppurativa (HS) is a chronic inflammatory disorder that is characterized by recurrence, as well as the characteristic location of skin lesions. Patients usually develop very painful inflammatory nodules that generally end in the formation of multiple abscesses and fistulas that typically occur in the skin of the axillary, inguinal, buttock, and perianal folds. It significantly affects the quality of life of patients, leaving physical, economic and psychological sequelae. There is a wide therapeutic arsenal available, but each patient must be individualized and the best possible treatment determined. Early assessment and intensive treatment of the disease can prevent and even avoid significant sequelae and permanent deformities.